Association between locomotive syndrome and blood parameters in Japanese middle-aged and elderly individuals: a cross-sectional study - Toshinori Yoshihara; Hayao Ozaki; Takashi Nakagata; Toshiharu Natsume; Tomoharu Kitada; Yoshihiko Ishihara; Shuji Sawada; Masayoshi Ishibashi; Hiroyuki Kobayashi; Shuichi Machida; Hisashi Naito (BMC Musculoskeletal Disorders, 2019)
Abstract Background Locomotive syndrome (LS) is associated with weakness and loss of function in the musculoskeletal organs. We aimed to determine the association between LS components and blood parameters in middle-aged and elderly individuals. Methods We included 223 middle-aged and elderly individuals in this study (104 men and 119 women; age: 40–85 years). All participants were asked to fast for at least 3 h before the venous blood samples were obtained and the hemoglobin, total protein, glycated hemoglobin (HbA1c), growth hormone, albumin and lipid profile were measured. Three functional tests, the stand-up test, the two-step test, and the 25-question geriatric locomotive function scale (GLFS) were used to assess the risk of LS. Walking speed was assessed by the 10-m walking test. Maximal isometric muscle strengths of the knee extensors were examined, and the weight bearing index (knee extension strength/body weight) was calculated. To assess an independent association between blood parameters and LS, the area under the receiver operating characteristic curve analysis (area under the curve, sensitivity, and specificity) and a binary logistic regression analysis were performed with adjustment for age. Results Of the 223 subjects, 119 (53.3%) fulfilled the diagnostic criteria for LS (including a two-step test score < 1.3, difficulty with one-leg standing from 40 cm in the stand-up test, and a 25-question GLFS score ≥ 7). Increased levels of HbA1c were significant risk factors for LS with an OR of 2.62 (OR95%CI = 1.43–4.80), as determined by a logistic regression analysis. Additionally, dehydroepiandrosterone-sulfate (DHEA-S) levels were significant only in the male subjects (OR = 0.992 [OR95%CI = 0.986–0.998]), at a threshold of 88 (AUC; 0.70, sensitivity; 79.6%, specificity; 49.1%). Moreover, 101 of 223 participants (41 men, 60 women) were analyzed for serum albumin levels, with a prevalence of LS at 55.4%, indicating that low levels of albumin were significant risk factors for LS (OR = 0.148 [OR95%CI = 0.023–0.954], p = 0.0445). Conclusions These results suggest that higher HbA1c and lower albumin are associated with the prevalence of LS in Japanese middle-aged and elderly individuals. Furthermore, low DHEA-S levels may be useful screening tools for LS in men.